The Effectiveness of Asiatic Acid, Asiaticoside, and Madecassocide in Centella Asiatica, (Linn), Urb. on the Healing Process of Infected Wounds in Experimental Animals: Systematic Literature Review - Kessyy Widowati; Evi Lusiana; Theodorus; Debby Handayati Harahap; Nita Parisa; Abda Arif (Sriwijaya Journal of Medicine, 2024)
A wound is a condition where body tissue is damaged as a result of sharp objects, chemicals, animal bites, electric shocks, and so on. Good and correct wound management can prevent wounds from becoming infected. In general, for infected wounds, aminoglycoside antibiotic ointments are used which are effective against gram-negative and gram-positive bacteria, such as gentamicin. Where the use of gentamicin ointment is still the "Drug of Choice" for infected wounds. However, due to several side effects that can be caused such as allergic reactions that will cause discomfort in patients with hypersensitivity to antibiotics in this group and the possibility of resistance to the use of this type of antibiotic, other alternative therapies have emerged for treating wounds with ingredients that have minimal side effects, one of which is by using traditional medicine from nature. One of the herbal medicines that is believed to be able to treat skin wounds is the Gotu Kola plant or Centella asiatica. The gotu kola plant or Centella asiatica contains several active substances that are useful in accelerating wound healing, namely Asiatic acid, Madecassocide, and Asiaticoside. This study aims to determine and assess the activity of these substances in Centella asiatica which play a role in the healing process of infected wounds in experimental animals. This research is a review article, by searching data from Google Scholar, PubMed, and NCBI databases with keywords used such as, "Effectiveness of Centella, Active Ingredients of Centella, Centella on Wounds". Many articles appear, but those used in this article that fit the inclusion criteria are 6 articles. The results of the 6 articles stated that Centella asiatica has the potential to heal infected wounds because it contains triterpenoid compounds which have antibacterial activity against Staphylococcus aureus and Escherichia colli. This review article concludes that the active substances found in pegagan leaves, namely Asiatic acid, Madecassocide, and Asiaticoside, have benefits in healing infected wounds in experimental animals.